2013
DOI: 10.4103/0973-029x.110720
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiological profile of oral potentially malignant and malignant conditions among areca nut, tobacco and alcohol users in Eastern India: A hospital based study

Abstract: Context:With an increase in the abuse of various oral habitual products in India over the past few decades; the incidence of oral potentially malignant conditions as leukoplakia, oral submucous fibrosis and squamous cell carcinoma (SCC) rates have also increased. No recent study has been conducted reporting the scenario of oral cancer and potentially malignant conditions in Eastern India (specifically Kolkata).Aims:The present study was conducted at Dr. R. Ahmed Dental College, Kolkata during 2010-2011 to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
(16 reference statements)
3
17
0
Order By: Relevance
“…17 Likewise, the gender predominance was similar to the findings of J G Ray et al, and Shrestha A et al, who found occurrence of OSMF more in males as compared to females. 17,18 Moreover, the mean age of the subjects with OSCC (Group III) was 50.04 years, with a peak incidence in 5th and 6th decades of life. This finding was similar to the findings of Ku K T et al, who stated the mean age of OSCC patients as 52 years.…”
Section: Discussionsupporting
confidence: 87%
“…17 Likewise, the gender predominance was similar to the findings of J G Ray et al, and Shrestha A et al, who found occurrence of OSMF more in males as compared to females. 17,18 Moreover, the mean age of the subjects with OSCC (Group III) was 50.04 years, with a peak incidence in 5th and 6th decades of life. This finding was similar to the findings of Ku K T et al, who stated the mean age of OSCC patients as 52 years.…”
Section: Discussionsupporting
confidence: 87%
“…Tobacco, when used together with areca nut, can act synergistically and exert more severe adverse effects on the mucosa; they can cause increased dryness of the oral mucosa, thereby, increasing the systemic absorption of metabolites, and triggering the occurrence of BQLL. 16 A higher percentage of subjects (88%) chewed processed forms rather than the raw or unprocessed forms of quid, in the present study. The MNLR analyses revealed that individuals who chewed both processed and unpro-cessed forms of quid were three times more likely to develop BQLL + QOML, when compared to those who chewed the processed form only.…”
Section: Discussionmentioning
confidence: 39%
“…Furthermore, the likelihood of developing BQLL + QOML was nine times higher in patients who chewed quid comprising both tobacco and areca nut, when compared to those who chewed tobacco alone. Tobacco, when used together with areca nut, can act synergistically and exert more severe adverse effects on the mucosa; they can cause increased dryness of the oral mucosa, thereby, increasing the systemic absorption of metabolites, and triggering the occurrence of BQLL …”
Section: Discussionmentioning
confidence: 99%
“…In eastern India, different forms of tobacco addictions are popular such as khaini, gudakhu, snuff, bidi, paan and gutkha. A recent study reported that males with the habit of smokeless tobacco or mixed habit had the highest risk for developing OSCC while in females, it was associated with addiction of chewing processed areca nut [24].…”
Section: Discussionmentioning
confidence: 99%